SEISMIC DATA PROCESSING WITH CONTAMINATED MULTIPLE USING CRS METHOD - RAHMANSYAH (NIM: 12405012), ARI
Imaging of subsurface conditions can be done by processing seismic data. At the stage of imaging subsurface reflector must take into account factors of undulations and the slope of the reflector as it will result in the hyperbolic curve flatter than the travel time equation for a flat reflector. The more steep a hyperbolic reflector then the curve will be more ramps. To solve this problem, the effect undulating reflector needs to be included in the calculation of travel time in the form of hyperbolic curves. Tygel et al (1997) expands the function of travel time using a Taylor series up to second order, so that the curvature of the interface can be contained in it. This hyperbolic curve is called the Common Reflection Surface stacking curve (CRS stacking curve). In this final assignment the analysis will be done on the conventional seismic method and the method of the Common Reflection Surface (CRS) which carried to the stages of migration, especially the Pre-Stack Time Migration. Because the data in CRS method tends to strengthen the multiple then demultiple had to be done to eliminate the existing multiple using parabolic radon transformation.